A new system to study directional volatile-mediated interactions reveals the ability of fungi to specifically react to other fungal volatiles - Bruisson, Sébastien; Alfiky, Alsayed; L'Haridon, Floriane; Weisskopf, Laure (Frontiers in Ecology and Evolution, 2023)
Microbes communicate with each other using a wide array of chemical compounds, including volatile organic compounds (VOCs). Usually, such volatile-mediated interactions are studied by growing two different microbes in a shared, confined environment and by subsequently collecting and analyzing the emitted VOCs by gas chromatography. This procedure has several drawbacks, including artificial volatile overaccumulation and potential oxygen limitation, as well as the impossibility to assign a producer to the compounds newly emitted during the interaction. To address these challenges, we have developed a novel system specifically designed to analyze volatile-mediated interactions allowing for sequential unidirectional exposure of a “receiver” microorganism to the VOCs of an “emitter” microorganism. Using hermetically sealed systems connected to an air compressor, a constant unidirectional airflow could be generated, driving emitted volatiles to be absorbed by a collection charcoal filter. Thus, our developed system avoids artificial overaccumulation of volatile compounds and lack of oxygen in the headspace and enables the univocal assignment of VOCs to their producers. As a proof of concept, we used this newly developed experimental setup to characterize the reaction of plant growth-promoting and biocontrol fungus (Trichoderma simmonsii) to the perception of VOCs emitted by two plant pathogens, namely Botrytis cinerea and Fusarium oxysporum. Our results show that the perception of each pathogen's volatilome triggered a specific response, resulting in significant changes in the VOCs emitted by Trichoderma. Trichoderma's volatilome modulation was overall stronger when exposed to the VOCs from Fusarium than to the VOCs from Botrytis, which correlated with increased siderophore production when co-incubated with this fungus. Our newly developed method will not only help to better understand volatile-mediated interactions in microbes but also to identify new molecules of interest that are induced by VOC exposure, as well as the putative-inducing signals themselves.